Adjustable transobturator sling for the treatment of primary stress urinary incontinence. (September 2018) - Shkarupa, Dmitry; Kubin, Nikita; Staroseltseva, Olga; Shapovalova, Ekaterina
Abstract Introduction and hypothesis The purpose of the study was to evaluate the rate of postoperative voiding dysfunction after the insertion of an adjustable transobturator sling for the treatment of primary stress urinary incontinence (SUI). The secondary aim was to assess the objective and subjective cure rates and the impact of the surgery on quality of life. Methods This prospective study included 171 patients with primary SUI who underwent insertion of an adjustable transobturator tape. A postoperative tension adjustment algorithm that included a cough stress test (CST), uroflowmetry and postvoid residual volume (PVR) measurement was applied in all patients the day after surgery. The baseline and control postoperative evaluations included vaginal examination, CST, Q-tip test, uroflowmetry and PVR measurement, 1-h pad test and administration questionnaires (UDI-6, IIQ-7, PISQ-12, ICIQ-SF). Results The day after surgery 65 patients (38.0%) required tape tension adjustment: an increase in tension in 53 patients (31.0%) and a decrease in 12 (7.0%). Continence was achieved in all patients. No patients showed voiding dysfunction after adjustment. Follow-up data for 12 months were available in 157 patients (91.8%). The objective and subjective cure rates were 96.2% and 97.5%, respectively. There was no statistically significant decrease inQ max (p = 0.899) or increase in PVR (p = 0.187). According to the questionnaires scores, quality of life was improved in all patients. Conclusion The adjustable transobturator sling minimizes the risk of postoperative voiding dysfunction and allows high objective and subjective cure rates to be achieved in patients with primary SUI. The technique also improves the patient's quality of life.